PENGARUH KUALITAS PELAYANAN, CITRA MEREK DAN LOKASI TERHADAP KEPUASAN PELANGGAN: (Studi pada Pelanggan After Sales PT Srikandi Diamond Motors Alam Sutera di Tangerang) - Suzette Natasha; Ravindra Safitra Hidayat (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
This research aims to determine whether the independent variables, namely service quality (X1), brand image (X2), and location (X3), influence the dependent variable, customer satisfaction (Y). The research population consists of customers of PT Srikandi Diamond Motors Alam Sutera in Tangerang. Total of 100 respondents were selected using purposive sampling technique. Data were collected through a Likert scale (1-5) questionnaire and analyzed using SPSS version 29. The respondent data collected in this study have been tested for data instrument validity and reliability, classic assumption tests (normality, multicollinearity, and heteroskedasticity), and simple correlation tests. The analytical method used was multiple linear regression. The research findings indicate that service quality significantly influences customer satisfaction with an improvement contribution of 0.226. Brand image influences customer satisfaction with an improvement of 0.414. Location influences customer satisfaction with an improvement of 0.154. These three independent variables affect customer satisfaction with a percentage of 74.3%, while 25.7% is influenced by other variables not covered in this research. Hence, service quality, brand image, and location are proven to significantly affect customer satisfaction at PT Srikandi Diamond Motors Alam Sutera in Tangerang.